Sistema de geração distribuída fotovoltaico integrado a um condicionador de qualidade de energia unificado monofásico-trifásico aplicado a áreas rurais ou remotas - Pelz, Guilherme Masquetti (2018)
This work presents the study and computational development of a distributed generation system composed of a two-stage photovoltaic system, which operates integrated by a four-wire three-wire local distribution system implemented by means of a single-phase-to-three-phase Unified Power Quality Conditioner. The proposed system, called PV-UPQC-Mono-Tri, in addition to allowing the photovoltaic power generation, is indicated to feed three-phase four wire loads for applications in rural or remote areas in which, for economic reasons, only single-wire earth return is accessible to the consumer. Simultaneously, the proposed system improves the power quality supplied to the consumer, as sags, swells, voltage regulation, among others, and, at the same time, drains or injects current in the single-phase grid with high power factor and low THD. A dual compensating strategy is adopted to operate the PV-UPQC-Mono-Tri system, where the parallel converter is controlled to act as a sinusoidal voltage source, while the series converter is controlled to operate as a sinusoidal current source. To ensure that the grid current and the voltage provided to the loads are sinusoidal, multi-resonant state-feedback, controllers are implemented. The coupling between the PV-UPQC-Mono-Tri DC-bus and de PV array is implemented by a DC-DC Boost converter, which is responsible for the PV array voltage control, according to the reference voltage calculated by the P&O MPPT algorithm. To control the PV array voltage, is used a multi-loop PI controller, and design procedures to this controller are presented. Simulation and experimental results are presented to evaluate both static and dynamic performances of the proposed PV-UPQC-Mono-Tri system.